Multi-Dimensional Activity Based Integrated Approach : An Innovative Teaching-Learning Strategy at the School Stage - Panda, B.N.; Basantia, Tapan Kumar (THE PRIMARY TEACHER, 2008)
Teaching-learning aims at bringing holistic and maximal development of students. To achieve this holistic and maximal development, a number of subjects are taught in our schools under different curricular and cocurricular heads, and different teaching-learning strategies are used for teaching the same subject. It is a fact that the nature of one subject is different from nature of other subjects, nature of one topic under same subject is different from nature of other topics, and the nature of one learning paragraph/unit under same topic is different from nature of other learning paragraphs/units. Hence, our teaching–learning strategy needs to be changed in accordance with the change in subjects, change in topics and change in learning paragraphs/units. Also, our teaching-learning strategy needs to be changed in accordance with the change in situation/endeavour, change in time, change in learners’ needs, change in demands of the society and change in philosophy of the country. In this article a new and innovative teaching–learning strategy, i.e. multi dimensional, activity based, integrated approach is discussed. This approach is learner–friendly, flexible, innovative and eclectic in nature and it may have wide implications for achieving the broad based objectives in different areas of teaching–learning with respect of attaining multisided devoplement among the learners